MRP, EOQ, JIT... y ahora ¿por dónde empiezo? - Córdova Zela, Petter (1997)
Case study in the logistics area of a large mining company. A professional who has worked for several years in the area of the company describes the main deficiencies of the system that underlie the daily problems. After some years away from the company, he returns as a consultant and finds that the company is in the process of privatization and must optimize its administrative and management systems in order to reduce costs and facilitate the transfer process. In this time, the problems that he had identified had been solved in part, and some elements of the environment had changed. A section of annexes is included that contains the description of the logistics system, the proposed replacement model and the way in which the Purchasing department is organized.